The Administrative Component in Growing and Declining Organizations: A Longitudinal Analysis - Ford, Jeffrey D. (Academy of Management Journal, 1980)
In a longitudinal study on 24 school districts the analysis of data over a 10-year-period indicates that (1) the relationship between size and the administrative component observed in cross-sectional designs does not obtain when organizations are individually analyzed and (2) relationships between size and personal components in declining school districts do not parallel those observed in growing districts.